2019
DOI: 10.1108/jaee-03-2018-0025
|View full text |Cite
|
Sign up to set email alerts
|

A meta-analysis approach for determinants of effective factors on audit quality

Abstract: Purpose The purpose of this paper is to demonstrate a deeper understanding about the reasons behind difference in previous studies’ results in the field of audit quality determinants. Design/methodology/approach A meta-analysis method is employed in which 52 studies including 40 international studies from authentic scientific articles… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
69
0
14

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 73 publications
(89 citation statements)
references
References 106 publications
6
69
0
14
Order By: Relevance
“…One of the potentialities for inconsistent findings of this paper, in comparison to previous outcomes, might come from the business environment of the Tehran stock exchange. For instance, CEO ability [71], auditor characteristics [15], and ownership structure [72] are among the effective factors on firm performance in the Iran market environment. Therefore exclusion of these explanatory variables may result in a different conclusion.…”
Section: Discussionmentioning
confidence: 99%
“…One of the potentialities for inconsistent findings of this paper, in comparison to previous outcomes, might come from the business environment of the Tehran stock exchange. For instance, CEO ability [71], auditor characteristics [15], and ownership structure [72] are among the effective factors on firm performance in the Iran market environment. Therefore exclusion of these explanatory variables may result in a different conclusion.…”
Section: Discussionmentioning
confidence: 99%
“…The Australian evidence supports a positive relationship between audit partner tenure and audit quality (Fargher et al, 2008). Based on the meta-analysis approach, Salehi et al (2018) observed that there is no significant relationship between auditor tenure and audit quality.…”
Section: Related Literature and Hypothesis Developmentmentioning
confidence: 92%
“…Hamid, (2013) states that a short alliance period makes auditors short of time to understand the client's business environment so that they are less able to better assess information. The results of research by Salehi et al, (2019), Junaidi et al, (2012), and Siregar et al, (2012) tenure audit affect audit quality. Refers to the results of research that has been done, the hypothesis is audit tenure positively affects audit quality.…”
Section: Introductionmentioning
confidence: 98%